Novosti v omrežju samopostrežnih terminalov sistema KZZ - Sušelj, Marjan (Informatica Medica Slovenica, 2002)
Self-service terminals network is a representative of the biggest data networks in Slovenia and enables data transfer between more than 260 locationsand central point in Ljubljana. Relatively full coverage of the territory and positive experiences in previous usage of services make the introduction of new services in the health care area and the connecting to other Slovene networks feasible.
Keywords: baze podatkov; Bolnik, identifikacijski sistemi; Computer Communication Networks; informacijski sistemi; Insurance, Health; Patient Identification Systems; Računalniške mreže; terminali; Zavarovanje zdravstveno; zdravstvena kartica; zdravstveno zavarovanje; zdravstvo